Are Muslims practising moderation in their financial decisions? - Ramlee, Roslily; Syed Mohd Zain, Sharifah Raihan; Wan Husain, Wan Rohaida (Penerbit Universiti Sains Malaysia, 2019)
Statistics and a survey of the literature revealed the existence of a massive problem in the financial prudence of Malaysians, including Muslims. One glaringly prominent aspect is the absence of a spiritual/religious interventionist approach in exploring the lack of consumer awareness that led to the present situation. Instead of attempting to solve the problem through brute economic policies, a wasatiyyah-oriented approach is warranted for informing consumers of their religious obligation to avoid profligate spending and adopt moderation in financial matters. Hence, the objective of this study is to examine the practice of moderation (the concept of wasatiyyah) among Muslims consumers in their financial decision-making. Primary data were collected through a self-administrated survey on a selected group of Muslim consumers. A relevant statistical software was employed to perform exploratory-factor analysis (EFA) through principal-component analysis (PCA), confirmatory factor analysis (CFA), and structural equation modelling (SEM) on the collected data. The findings demonstrated that moderation (wasatiyyah) partially mediates the relationship between materialism and financial decisions. Consequently, Muslim consumers who practice moderation while making their financial decisions are more conscious of their credit management and thus spend according to their means.